Renormalization group determination of the five-loop effective potential for massless scalar field theory - Chishtie, F A; McKeon, D G.C.; Steele, T G (Canadian journal of physics, 2008)
The five-loop effective potential and the associated summation of subleading logarithms for O(4) globally symmetric massless λφ 4 field theory in the Coleman-Weinberg renormalization scheme d 4 V / dφ 4 | φ=μ = λ (where μ is the renormalization scale) is calculated via renormalization-group methods. An important aspect of this analysis is conversion of the known five-loop renormalization-group functions in the minimal-subtraction (MS) scheme to the Coleman-Weinberg scheme.PACS Nos.: 11.30.Qc, 11.10.Hi, 11.15.Tk, 12.15.Lk